ENTERPRISE RISK MANAGEMENT DALAM MITIGASI KETIDAKSEIMBANGAN SUPPLY-DEMAND DAN RANTAI PASOK TERHADAP KEPAILITAN MELALUI FINANCIAL DISTRESS - Sholihah , Imroatus; Darmayanti, Novi; Nurhidayat, Esti (E-Jurnal Akuntansi TSM, 2025)
The imbalance of supply-demand and supply chain disruptions pose significant challenges to business sustainability, particularly in capital-intensive and export-oriented industries such as textiles. This study aims to analyze the role of Enterprise Risk Management (ERM) in mitigating the impact of supply-demand imbalance and supply chain disruptions on corporate bankruptcy risk through financial distress. Secondary data were collected from the financial reports of PT Sri Rejeki Isman Tbk (Sritex) during 2013–2023 and analyzed using the Ordinary Least Squares (OLS) regression method. The results show that supply, demand, and supply chain disruption variables significantly affect financial distress. Furthermore, financial distress serves as a mediator in the relationship between operational shocks and bankruptcy potential. These findings highlight the necessity of a structured ERM approach to respond to both internal and external pressures, rather than relying solely on historical financial indicators. The study implies that strengthening a company’s risk management system is crucial to enhancing resilience and mitigating bankruptcy potential in volatile environments. A comprehensive ERM framework can offer long-term financial stability.